Environmental Bioremediation Technologies - Singh, S.N; Tripathi, R. D. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Environmental contamination from both natural and anthropogenic sources is, today, a major environmental concern due to pervasiveness and persistence of many toxicants. It is considered as an inevitable evil of our progress and modernization. To decontaminate the soils, sediments and waters, polluted by anthropogenic activities, the scientists and technologists have evolved different technologies over the years. Although we have to pay high cost for physical and chemical environmental technologies, but they are not eco-friendly and safe. Hence, it was deeply realized to develop viable technologies employing microbes and plants to remediate not only metallic residues and radionuclides, but also the xenobiotic compounds like PCBs, PAHs, PCPs, petroleum sludge and the military wastes. No doubt, the scientists have also got some success in this endeavour and as the result, many companies are in place today to promote the sale of plant or microbe-based technologies to deal with specific environmental contamination challenges. Besides, these technologies are se- driven and do not disturb the sites in cleaning process.